Development of reference materials for composition of food dyes - D. H. Kulev; V. V. Bessonov; A. G. Nikolaev; N. V. Rudometova (Стандартные образцы)
Actuality of the research. Development of standard samples (SS) of food colour content continues to be relevant to enhance safety and quality of food products, additives and other micro-ingredients as well as to deal with import substitution. Work objective. The objective of this work is to develop SS for the basic substance and toxic elements in the most frequently used in food technologies synthetic food colours: Tartrazine E102, Yellow Quinoline E104, Azorubine E122 and Ponseau 4R E124. Research techniques. Mass fraction of colour in the samples was determined by spectrophotometry as per 320502013 GOST Standard; colour samples for toxic elements were evaluated according to 26929-94 GOST Standard; content of lead and cadmium was determined by atomic absorption analysis defined in the GOST 30178-96, arsenic -by calorimetry as per GOST 26930-94, mercury - by flameless atomic sorption spectrometry according to MU № 5178-90, homogeneity and shelf life - in conformity with RMG 93-2009, GOST 8.531-2002 and Р 50.2.031-2003. Results. SS for the content of four food colours were developed based on the research findings. Their following metrological specification is given in the Table 6: mass fraction of the basic substance, %, fractional error limits (P = 0,95), S, %; content of toxic elements, mg/kg with fractional error limits, S, %.